2022
DOI: 10.5812/mejrh.119423
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Anthropometric Measurements of Iranian Medical Students for Estimating Sex and Stature

Abstract: Background: Stature and sex estimation according to surface anatomical landmarks is applicable for personal identification in forensic medicine. Objectives: The present study aimed to prepare a comprehensive reference of four main upper limb anthropometric dimensions in Iranian adults and make a formula for predicting sex and stature according to them. Methods: In this cross-sectional study, four main anthropometric dimensions of the upper limb, including arm length, forearm length, hand length, and hand width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Moreover, Bahraini [41] males outgrew other Middle East populations in the hand breadth with 88.9 mm whereas Omani [43] males appeared to have the smallest hand breadth with 77.6 mm. Iranian [42] females with a value of 78.4 mm and Jordanian [35] females with a value of 77.8 mm had the largest hand breadth average measurements, while Sudanese [37] females appeared to have the smallest hand breadth with 70.6 mm. As can be observed, Turkish [38] had the smallest difference between the male and female mean hand breadth with more than 2 mm gap, while most other Middle East populations had about 10 mm hand breadth difference in both genders.…”
Section: 1comparative Analysismentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, Bahraini [41] males outgrew other Middle East populations in the hand breadth with 88.9 mm whereas Omani [43] males appeared to have the smallest hand breadth with 77.6 mm. Iranian [42] females with a value of 78.4 mm and Jordanian [35] females with a value of 77.8 mm had the largest hand breadth average measurements, while Sudanese [37] females appeared to have the smallest hand breadth with 70.6 mm. As can be observed, Turkish [38] had the smallest difference between the male and female mean hand breadth with more than 2 mm gap, while most other Middle East populations had about 10 mm hand breadth difference in both genders.…”
Section: 1comparative Analysismentioning
confidence: 87%
“…This study compares the variations in hand anthropometric measurements of selected ten Middle Eastern populations. Overall, it can be observed that among these ten nations, Omani [43] and Saudi Arabian [39] males had the longest hand with 202.2 mm and 201.1 mm respectively, while Iraqi and Iranian [42] males' appeared to have the shortest hands with 187.36 mm and 188.2 mm respectively. In females, Saudi Arabian [39] and Egyptian [36] hands were the longest with 186.5 mm and 181.32 mm respectively, while Lebanese [40] and Jordanian [35] females' appeared to have the shortest hands with 171.0 mm and 171.3 mm respectively.…”
Section: 1comparative Analysismentioning
confidence: 88%